Evaluating the Effectiveness of Snakes and Ladders Media in Improving Algebra Learning Outcomes of Junior High School Students - Hidayani Hidayani; Putri Dini R. P; Faisal Eka M; Nika F Trisnawati; Ruslan Layn (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
Low algebra learning outcomes among junior high school students are often associated with the dominance of conventional lecture-based teaching methods that reduce student engagement and motivation during the learning process. Therefore, this study aims to evaluate the effectiveness of using snakes and ladders learning media to improve students’ algebra learning outcomes and classroom activity. This research employed a mixed-methods approach with a one-group pretest–posttest design involving 29 purposively selected grade VII A students of STATE JUNIOR HIGH SCHOOLNegeri 6 Kota Sorong in the 2024/2025 academic year. Data were collected through lesson plans, pretest and posttest assessments, student activity observation sheets, and documentation. Data analysis included Kolmogorov–Smirnov normality tests, mastery percentage analysis, N-Gain calculation, and classical observation percentages using SPSS. The results indicated an increase in the average student score from 7.72 in the pretest to 43.34 in the posttest, with student activity reaching 68% categorized as active and an N-Gain score of 0.41 indicating moderate improvement. However, the classical mastery level only reached 21%, which was still below the minimum mastery criterion (KKM) of 71. In conclusion, the snakes and ladders learning media was effective in increasing students’ motivation and participation in algebra learning, although further improvement is required to achieve optimal cognitive learning outcomes. Future studies are recommended to refine the instructional design, extend the implementation period, and involve larger samples to obtain stronger learning impacts. This study is limited by the use of a single-group design and a relatively small sample size, which may affect the generalizability of the findings.